A 15‐year experience with gastric neuroendocrine tumors: Does type make a difference?. Issue 5 (8th July 2016) - Postlewait, Lauren M.; Baptiste, Gillian G.; Ethun, Cecilia G.; Le, Nina; Cardona, Kenneth; Russell, Maria C.; Willingham, Field F.; Kooby, David A.; Staley, Charles A.; Maithel, Shishir K.
Abstract : Background: Gastric neuroendocrine tumors (GNETs) are rare and classified into three types by disease etiology and typical behavior. Methods: The aim was to describe outcomes after GNET resection at a single institution from 2000 to 2014, stratified by tumor type. Given the small patient number, P ‐values were not assigned. Results: Of 22 patients, 12 patients (55%) had Type 1, none (0%) had Type 2, and 10 (45%) had Type 3 tumors. Compared to Type 3, Type 1 patients were younger (mean age: 52 vs. 59 years) with similar rates of endoscopic resection (25% vs. 20%). Type 1 GNETs often had multiple tumors (60% vs. 10%) and were not poorly differentiated (0% vs. 11%). Only 33% of Type 1 had nodal metastases compared to 71% of Type 3. Type 1 GNETs presented with metastatic disease less often (17% vs. 40%). Three year recurrence‐free survival was 33% for Type 1 compared to 86% for Type 3. Disease‐specific survival at 3‐years was 100% and 75% for Types 1 and 3, respectively. Conclusion: Type 1 GNETs are often indolent and multifocal without nodal involvement, but have high recurrence risk. Type 3 is more aggressive with increased nodal involvement; nodal evaluation should be routinely performed. Determination of GNET type is paramount to treating patients with this rare disease. J. Surg. Oncol. 2016;114:576–580 . © 2016 Wiley Periodicals, Inc.